Building a virtual framework to exploit multidisciplinary project workshops – peaks & pits - Turcsányi-Szabó, Márta; Abonyi-Tóth, Andor; Ekker, Nikoletta (Teaching Mathematics and Computer Science, 2013)
Multidisciplinary project work in connection to industry is highly favoured at University education, since it prepares students to envision their spectrum of profession, to be able to participate in production projects in co-operation with partners out of campus, and learn to communicate between disciplines. An effctive combination presumes selection of right partners, set-up of proper virtual platform to bridge time, space, and diffrences in working styles. The set-up process requires several phases of design-based research proofing the melding process to produce a productive workshop that is sustainable. The paper describes the review of literature, the platform and set-up established, a first phase in bridging Art and Computer Science through the description of MOMELTE project, a critical evaluation in order to learn from mistakes, and a new list of design principles to improve the next phase of the workshop process.